Pilgrims and their money on the way to Rome. The evidence of the Libro del pellegrino (Siena, 1382–1446) (Theatrum historiae, 2010)
The pilgrim book (Il Libro del pellegrino) of the hospital of Our Lady della Scala in Siena from 1382–1446 represents an accurately guided document on monetary deposits in one of the most important church institutions in Siena. A large-scale set of specie registered in this book is an interesting witness to the movement of money in circulation in late me- dieval Europe. Seven pilgrims from the lands of the Bohemian Crown are mentioned in the entries from 1384–1433: two come from Bohemia, four from Moravia and one from Sile- sia. Further two other pilgrims with an ambiguous geographic assignment seem to be con- sidered. The book, however, does not register all pilgrims who visited Siena on the way to Rome. It mentions only those who deposited their cash in the hospital with the intention to withdraw it on the way back. The writer compares registered deposits with amounts intended for the pilgrimage to Rome (4–5 pounds of Prague groschens in the lower middle class and 8–10 pounds in the higher middle class) which have been entered into the memorable city book of Olomouc dated back to 1430–1492. He distinguishes sums intended to the way back (1,5–8 pounds) from petty cash (within the range of 4–35 Prague groschens) which could suffice for just few days. At average speed of 40 km per day it is possible to suppose that the journey from the Czech lands to Rome (about 1 300 km) could last about 37–38 days with 5–6 days of rest. At average expense of 3 Prague groschens per day which roughly corresponds with the most common summer daily wage of a journeyman, a pilgrim was able to manage for about 85 days with 4 pounds of Prague groschens, it was enough for a return journey and for about ten days ́ stay in Rome. If he took 5 pounds with him he could stay in Italy for one month. A double amount of 8–10 pounds presumably served as a nest-egg for the case of illness or of accident. In better case it could provide travel luxury. Contrary of the testimonies it is not possible to judge from deposits of the social status of their bearers. Money of pilgrims predominantly consisted of gold coins contained in more than 70 % of all registered deposits. Larger amounts were mostly deposited by those pilgrims who were coming from the far-away regions and by old priests who started on a journey with all their belongings in conviction not to come back any more. That is a case of Florian of Kočov, chaplain in Volyně (South Bohemia), who gave 20 florins into custody of friars in Siena. The entries in the pilgrim book of Siena document that Florentine florins, Venetian ducats and Hungarian florins belonged to the most frequent gold specie in Italy that time, Prague and Flemish groschens occurred most often among silver coins. From the given data which mention a value of money very sporadically it is, however, not possible to make even an approximate estimation of the sum total of money which flew into the hospital. We can just suppose that the sum total of 2 500 florins which represent the value of all 328 deposits registered by 1410 did not get entire to the hospital treasury because many deposits have been withdrawn in the meantime. Just a part of them remained after those pilgrims who died in the hospital and whose deposits have never been withdrawn. Nevertheless, it was still a relatively large amount which was continuously becoming a hospital ownership.